2017
DOI: 10.1007/s13239-017-0324-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Left Ventricular Blood Flow Using Smoothed Particle Hydrodynamics

Abstract: This study aims to investigate the capability of smoothed particle hydrodynamics (SPH), a fully Lagrangian mesh-free method, to simulate the bulk blood flow dynamics in two realistic left ventricular (LV) models. Three dimensional geometries and motion of the LV, proximal left atrium and aortic root are extracted from cardiac magnetic resonance imaging and multi-slice computed tomography imaging data. SPH simulation results are analyzed and compared with those obtained using a traditional finite volume-based n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 58 publications
(61 reference statements)
2
50
0
Order By: Relevance
“…This limited imposition is likely to affect the flow solution in the boundary layer and limit the study of the small‐scale flow features seen in the cardiac flow. However, previous studies have shown that the large‐scale intraventricular hemodynamics as well as the cardiac tissue and heart valve mechanics obtained using the proposed SPH‐based FSI method are in agreement with in vivo, in vitro, and in silico measurements …”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This limited imposition is likely to affect the flow solution in the boundary layer and limit the study of the small‐scale flow features seen in the cardiac flow. However, previous studies have shown that the large‐scale intraventricular hemodynamics as well as the cardiac tissue and heart valve mechanics obtained using the proposed SPH‐based FSI method are in agreement with in vivo, in vitro, and in silico measurements …”
Section: Discussionsupporting
confidence: 51%
“…The other two studies validated the coupled dynamics of the subject‐specific LH model with normal LV function and no heart valve abnormalities. A quantitative comparison of FSI results with a traditional finite volume‐based numerical method, in vivo phase‐contrast magnetic resonance imaging, and echocardiography data demonstrated that the SPH‐FE approach was able to simulate the coupled kinematics of the AV and MV, and the large‐scale intraventricular blood flow phenomena …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three approaches have been proposed toward the characterization of LV wall motion and resulting hemodynamics using this strategy. The first approach, which consists of imposing a new mesh at each time step, is hampered by a poor accuracy due to the numerical errors resulting from the interpolation of the flow field from one grid to the next (Khalafvand et al, 2012;Nguyen et al, 2013;Caballero et al, 2017). To relax this challenge, another approach consists of applying directly local displacements to the fluid domain boundary via node-to-node mapping or correlation algorithms (Su et al, 2014b;Bavo et al, 2016;Lai et al, 2016;Doost et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Medical applications using the SPH method have started to appear very recently. For example, interactive blood simulations for virtual surgery using the SPH method have been performed by Muller et al [15], while SPH of left ventricular blood flow has been reported by Caballero et al [16]. Although, computational hemodynamic analyses of endovascular devices have been performed using conventional methods [17] [18] [19], so far no simulations with SPH exist in the literature.…”
Section: Introductionmentioning
confidence: 99%